Common Causes of Neonatal Jaundice –A Study of 100 Cases at Neonatal Unit of Rajshahi Medical College Hospital (TAJ: Journal of Teachers Association, 2018)
A prospective cross sectional study was done at Neonatal unit of Rajshahi Medical College Hospital, from 01/01/15 to 30/06/15 period. Total 100 neonates with jaundice were included in this study. Causes of Jaundice were physiological 35%, sepsis 20%, prematurity 15%, perinatal asphyxia 8%, ABO incompatibility 8%, Rh-incompatibility 5%, unknown 9%.TAJ 2013; 26: 1-2